2009
DOI: 10.1007/s10926-009-9194-z
|View full text |Cite
|
Sign up to set email alerts
|

Age and Disability Employment Discrimination: Occupational Rehabilitation Implications

Abstract: Introduction As concerns grow that a thinning labor force due to retirement will lead to worker shortages, it becomes critical to support positive employment outcomes of groups who have been underutilized, specifically older workers and workers with disabilities. Better understanding perceived age and disability discrimination and their intersection can help rehabilitation specialists and employers address challenges expected as a result of the evolving workforce. Methods Using U.S. Equal Employment Opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 17 publications
0
45
0
3
Order By: Relevance
“…Finally, Bjelland et al [16] argued that older workers and workers with disabilities are underutilized groups that can help employers address the worker shortage challenge expected as a result of the changing demographics and evolving workforce. They analyzed the U.S.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Bjelland et al [16] argued that older workers and workers with disabilities are underutilized groups that can help employers address the worker shortage challenge expected as a result of the changing demographics and evolving workforce. They analyzed the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Equal Employment Opportunity Commission (EEOC) Employment Discrimination Charge Data to examine perceived age and disability discrimination and their intersection to help employers better understand age and disability discrimination issues. Bjelland et al [16] found that employment discrimination claims that originate from older or disabled workers are concentrated within a subset of issues that include reasonable accommodation, retaliation, and termination. They also found that small firms are most vulnerable for age and disability discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that chronic conditions increase with age and with that many comorbid mental health conditions (Keyes, 2005). Employees are choosing to remain employed longer and aging workers are one of the fastest growing groups in the workforce today (Bjelland et al, 2010;Toossi, 2007). Estimates from the United States (US) Bureau of Labor Statistics report that between 2006 and 2016 workers aged 55 and older will increase by 47% (Toossi, 2007).…”
mentioning
confidence: 99%
“…Age is another factor associated with economic outcomes (Bjelland et al, 2010;Lippmann, 2008;Roscigno, Mong, Byron, & Tester, 2007). In the original dataset, the variable YEAR registered the year in which the respondents were born.…”
Section: Immigration Statusmentioning
confidence: 99%